Post partum endothelin-1 and angiogenic factors causing persistent endothelial dysfunction in mothers with hypertensive disorders of pregnancy - Ismawi, Hidayatul Radziah; Mohd Zainudin, Maizura; Jamani, Nurjasmine Aida; Elshami, Taher FT; Abdul Razak, Tariq (2019)
Aims/Objective: The prevalence of hypertensive disorders of pregnancy (HDP) in Malaysia is approximately 23.3 per 1000 live births. It is also an independent risk factor of CVD with endothelial dysfunction postulated as the main pathophysiology. This study aims to determine serial ET-1, NO and other angiogenic factors in patients with HDP, and its role in persistent endothelial dysfunction. Methods: Thirty-six pregnant women from the following categories i.e. (i) normal pregnant women (control), (ii) chronic hypertension during pregnancy (CH) and (iii) gestational hypertension (GH) participated in this study. Blood pressure indices measurements and sample collection was done at antepartum (32 weeks) and postpartum (8 weeks and 12 weeks). ET-1 and serum NO were measured using the Human ET-1 (Endothelin-1) ELISA Kit and Nitric Oxide (total) detection kit, respectively. sFlt-1, PlGF and VEGF were measured by commercially available kits. A competitive NO antagonist, asymmetric dimethylarginine (ADMA) was measured using high performance liquid chromatography (HPLC). Results: Serum ET-1 was significantly higher in patients with CH (55.3 pg/ml) and GH (35.6 pg/ml) compared to control (11.8 pg/ml) during antenatal until three months postpartum (CH 38.3 pg/ml, GH 29.5 pg/ml, control 1.9 pg/ml); accompanied by significantly high levels of sFlt-1 in HDP subjects. Conversely, subjects with CH and GH had lower levels of serum NO, PlGF and VEGF (p < 0.05). Conclusion: Sustained NO/ET-1 imbalance and non-physiological levels of angiogenic factors in persistent endothelial dysfunction may account for increased CVD risk, despite normalisation of blood pressure. Screening and early detection will improve long-term cardiovascular health.